SOURCES OF ISLAMIC LAW: AN EPISTEMOLOGICAL STUDY AND ITS RELEVANCE IN THE CONTEMPORARY CONTEXT - Muhamad Ikhsanudin; Ruslaini; Zuhdiyah Zuhdiyah; Maryamah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The study of the sources of Islamic law is a crucial aspect in understanding the normative construction and the dynamics of its application amid complex social changes. This article aims to comprehensively elaborate on the four classical primary sources of Islamic law—namely the Qur’an, Sunnah, Ijma‘ (consensus), and Qiyas (analogical reasoning)—and to examine their epistemological relevance in contemporary contexts. The research employs a qualitative method with a library-based approach, focusing on critical analysis of both classical and modern literature concerning the epistemology of Islamic law. The findings indicate that the epistemological structure of Islamic law is dynamic, open to the process of ijtihad (independent reasoning), and capable of adapting to evolving social realities. In contemporary settings, challenges such as globalization, legal pluralism, and scientific advancement demand a reinterpretation of Islamic legal sources through interdisciplinary approaches. The study also identifies a methodological gap in Islamic legal studies, particularly in integrating maqāṣid al-sharī‘ah (objectives of Islamic law) with modern social sciences. Therefore, a new paradigm is needed to bridge the normative Islamic tradition with the needs of modern society, aiming to produce Islamic legal formulations that are more responsive, contextual, and oriented toward public welfare. This study is expected to enrich the discourse on the epistemology of Islamic law and encourage the development of more inclusive and transformative methodologies.